2018
DOI: 10.3415/vcot-17-01-0018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Radiographic Measurements of the Femur in Yorkshire Terriers with and without Medial Patellar Luxation

Abstract: Yorkshire Terriers affected with grade IV MPL had severe femoral deformities or femoral varus and external rotation of the distal femur. Reference range can be used as an aid in diagnosis, determining indications and surgical planning for corrective osteotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…Soparat et al [ 30 ], found no significant difference in ICA values in Pomeranians with and without MPL. The same results were reported by Olimpo et al [ 35 ], for different small-breed dogs; Yasukawa et al [ 36 ], for Toy Poodles; Lusetti et al [ 39 ], for English bulldogs; Newman and Voss, [ 40 ], for English Staffordshire bull terriers; Perry et al [ 41 ], for a combination of different dog breeds; Phetkaew et al [ 43 ], for Chihuahuas; and Žilinčík et al [ 44 ], for Yorkshire terriers. Perry et al [ 41 ], reported a significant association between increased ICA values and postoperative complications in dogs that had undergone MPL surgery.…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…Soparat et al [ 30 ], found no significant difference in ICA values in Pomeranians with and without MPL. The same results were reported by Olimpo et al [ 35 ], for different small-breed dogs; Yasukawa et al [ 36 ], for Toy Poodles; Lusetti et al [ 39 ], for English bulldogs; Newman and Voss, [ 40 ], for English Staffordshire bull terriers; Perry et al [ 41 ], for a combination of different dog breeds; Phetkaew et al [ 43 ], for Chihuahuas; and Žilinčík et al [ 44 ], for Yorkshire terriers. Perry et al [ 41 ], reported a significant association between increased ICA values and postoperative complications in dogs that had undergone MPL surgery.…”
Section: Resultssupporting
confidence: 73%
“…Eleven articles from a total of 29 articles were included in this group. The second group consisted of studies that compared the femoral and tibial alignments in different dog breeds with and without different orthopedic diseases, such as cranial cruciate ligament (CrCL) rupture, different grades of medial or lateral patellar luxation (MPL or LPL respectively), and osteoarthritis [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Eighteen articles were contained in the second group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations